N-3 Polyunsaturated Fatty Acids and Gut Microbiota - Jayapala, Hettiarachchige P. S.; Lim, Sun Y. (Combinatorial Chemistry & High Throughput Screening, 2023)
For several decades, studies have reported that n-3 polyunsaturated fatty acids (PUFAs) play a beneficial role in cardiovascular, immune, cognitive, visual, mental and metabolic health. The mammalian intestine is colonized by microbiota, including bacteria, archaea, viruses, protozoans, and fungi. The composition of the gut microbiota is influenced by long-term dietary habits, disease-associated dysbiosis, and the use of antibiotics. Accumulating evidence suggests a relationship between n-3 PUFAs and the gut microbiota. N-3 PUFAs can alter the diversity and abundance of the gut microbiome, and gut microbiota can also affect the metabolism and absorption of n-3 PUFAs. Changes in the populations of certain gut microbiota can lead to negative effects on inflammation, obesity, and metabolic diseases. An imbalanced consumption of n-3/n-6 PUFAs may lead to gut microbial dysbiosis, in particular, a significant increase in the ratio of Firmicutes to Bacteroidetes, which eventually results in being overweight and obesity. N-3 PUFA deficiency disrupts the microbiota community in metabolic disorders. In addition, accumulating evidence indicates that the interplay between n-3 PUFAs, gut microbiota, and immune reactions helps to maintain the integrity of the intestinal wall and interacts with host immune cells. Supplementation with n-3 PUFAs may be an effective therapeutic measure to restore gut microbiota homeostasis and correct metabolic disturbances associated with modern chronic diseases. In particular, marine extracts from seaweed contain a considerable dry weight of lipids, including n-3 PUFAs such as eicosapentaenoic acid (EPA, C20: 5) and docosahexaenoic acid (DHA, C22: 6). This review describes how gut microbiota function in intestinal health, how n-3 PUFAs interact with the gut microbiota, and the potential of n-3 PUFAs to influence the gut-brain axis, acting through gut microbiota composition.
Keywords: docosahexaenoic acid (DHA)